Stepwise strategy for generating human trophoblast stem-like cells from embryonic stem cells reveals specific role of TFAP2C in acquiring self-renewability - Masatoshi Ohgushi; Kaori Honda; Rina Takagi; Mototsugu Eiraku (Scientific Reports)
Abstract Human trophoblast stem cells (TSCs) can self-renew and differentiate into major trophoblast lineages. Although TSC-like cells can be derived from both naïve and primed pluripotent stem cells (PSCs), the mechanisms governing the conversion of PSCs into a TSC state remain only partially understood. This study explored the cellular properties of primed PSC-derived trophoblast stem-like cells (TSLCs) and the molecular processes underlying the PSC-to-TSLC conversion. We first induced GATA3+ cells from primed PSCs using small molecule inhibitors and then cultured them under defined TSC maintenance conditions. The resulting TSLCs exhibited transcriptomic similarity to established TSCs and villous cytotrophoblasts from the human first-trimester placenta and demonstrated bipotency toward major trophoblast subtypes. Notably, while GATA3+ cells lack self-renewal capacity, the TSC culture conditions facilitate their conversion into self-renewing TSLCs. Furthermore, the transcription factor TFAP2C was identified as essential for imparting self-renewal capacity to GATA3+ cells. These findings demonstrate that TSLC derivation from primed PSCs involves two distinct processes: trophoblast lineage fate conversion and self-renewal capacity acquisition, the latter of which is specifically dependent on TFAP2C.